A Power Tracking Algorithm for Early Detection of Centrifugal Flow Pump Thrombosis. Issue 9 (1st July 2021) - Slaughter, Mark S.; Schlöglhofer, Thomas; Rich, Jonathan D.; Brown, Michael C.; Kadrolkar, Abhijit; Ramos, Veronica; Stadler, Robert W.; Uriel, Nir; Mahr, Claudius; Sauer, Andrew J.
Abstract : Logfiles from the HeartWare HVAD System provide operational pump trend data to aid in patient management. Pump thrombosis is commonly associated with increases in the logfile power that may precede the clinical presentation. A Power Tracking algorithm was developed to detect significant deviations in pump power that may be associated with pump thrombus (PT). The Power Tracking algorithm was applied retrospectively to logfiles captured in the ENDURANCE, ENDURANCE Supplemental, and LATERAL clinical trials. From a combined dataset of 896 patients, available logfiles with suspected PT (n = 70 events in 60 patients) and available logfiles from patients without adverse events (AEs) (n = 106 patients, consisting of 27.4 patient-years of monitoring) were organized into two cohorts. The Power Tracking algorithm detected PT cases on or before the recorded AE date with a sensitivity of 85.7%, with detection occurring an average of 3.9 days before clinical presentation. The algorithm averaged one false alarm for every 6.85 patient-years of monitoring from logfiles without AEs. The favorable performance of the Power Tracking algorithm may enable earlier detection of pump thrombosis and allow early medical management versus surgical intervention.